Occupation and Sickness Absence in the Different Autonomous Communities of Spain - Alba Jurado, Matilde Leonor; Aguado Benedí, María José; Moreno-Morales, Noelia; Labajos-Manzanares, María Teresa; Martín-Valero, Rocío (MDPI, 2021)
The occupation of a worker is a determining factor of sickness absence (SA) and can influence both the beginning and continuation of the latter. This study describes SA in Spain, separately in the different Autonomous Communities (AC) in relation to the occupation of workers, with the aim of determining the possible differences in its frequency and duration, relating it also to the diagnosis. A total of 6,543,307 workers, aged 16 years and older, who had at least one episode of SA in the year 2019, constituted the study sample. The obtained results indicate that SA is more frequent and shorter in more elemental occupations. The average duration increases with age and is longer in women, except in technical and administrative occupations, where there is no gender divide. Sickness absences caused by musculoskeletal and mental disorders are more frequent in the lower occupational classes, although their average duration is shorter than in other, more qualified groups. The ACs with shorter duration in almost all the occupational groups are Madrid, Navarre and the Basque Country. In conclusion, SA is more frequent and shorter in lower occupational classes.
Keywords: Salud laboral; Trabajadores - Derechos; Sickness absence; Occupation health; occupational class; Autonomous Community